2018
DOI: 10.1111/dech.12398
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Social Performance: A ‘Practice Drift’ at the Frontline of Microfinance Institutions in Bangladesh

Abstract: This article examines the role of microfinance staff and procedures in enabling microfinance's social mission. It does so primarily through studying institutional ruling relations and practices in rural Bangladesh. Attempting to move away from the linear and deterministic approaches of impact studies, it ethnographically scrutinizes the everyday practices of implementers. Findings point to the emergence of systemic practices that jeopardize microfinance institutions' potential to perform their social mission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 86 publications
1
34
0
Order By: Relevance
“…Implies that MFI strives for profitability abandons the poor segment of the population from its portfolio. Hence, the trade-off relationship exists between MFI efficiency (financial performance) and serving low-income people (outreach) (Gonzalez, 2010;Maîtrot, 2019). Besides, small loan sizes and high transaction costs of serving the poorest are the immediate reasons for the MFIs' high-interest rate (Mersland & Strøm, 2010;Morduch, 2000;Rosenberg, Gonzalez, & Narain, 2009).…”
Section: Complementary (Positive) Relationshipmentioning
confidence: 99%
“…Implies that MFI strives for profitability abandons the poor segment of the population from its portfolio. Hence, the trade-off relationship exists between MFI efficiency (financial performance) and serving low-income people (outreach) (Gonzalez, 2010;Maîtrot, 2019). Besides, small loan sizes and high transaction costs of serving the poorest are the immediate reasons for the MFIs' high-interest rate (Mersland & Strøm, 2010;Morduch, 2000;Rosenberg, Gonzalez, & Narain, 2009).…”
Section: Complementary (Positive) Relationshipmentioning
confidence: 99%
“…However, the story to date provides important lessons about the role of regulation in the microfinance world, the impact of poorly conceived actions and their unintended consequences. Microfinance contexts underpinned by conflict market, development and regulatory logics (Khavul et al, 2013) Commercial banking logic displaces development logic (Kent & Dacin, 2013) Discursive abilities of policy makers shape new policy ideas (Schmidt, 2008) Contested discursive spaces (Hardy & Maguire, 2010) Material practice, organizing principles and symbolic constructions of an institutional field (Thornton & Ocasio, 2008) Policy (Merton, 1936) Issues are framed and contested between key actors (Schmidt, 2008) Organizational responses to conflicting institutional demands (Pache & Santos, 2010) Unanticipated consequences of institutional change (Lawrence et al, 2011) Practice drift: key practices of microfinance workers change (Maîtrot 2018) Prudential regulations aimed at protecting the financial system (Christensen & Rosenburg, 2000) Programmatic level: overseeing the sector (Schmidt, 2008) Microfinance can no longer serve the poor because of mission drift (Woller, 2002) The new world order: organisations based on aid and donations regarded as redundant (Fowler, 2000) Coercive institutional isomorphism (DiMaggio & Powell, 1983) Philosophical -means the provision of financial services primarily to micro or small enterprises and low income customers, usually characterised by the use of collateral substitutes except salaried backed loans; or any other services that the Bank may designate (p. 22)…”
Section: Resultsmentioning
confidence: 99%
“…Market logic shifted the focus onto financial sustainability and outreach through income generating activities; this is one foremost reasons for the criticism of some MFIs who have instead started to favour lower risk and marginally wealthier clients that yield a better financial return (Coleman, 2006;Copestake, Dawson, Fanning, McKay & Wright-Revolledo, 2005;Cull, Demirguc-Kunt & Morduch, 2007). This can lead to a deviation from the assumed social mission (Mersland & Strøm, 2010) where increased competition in the sector and a need to retain clients (Aubert, de Janvry, & Sadoulet, 2009) has placed greater emphasis on the finances of MFIs thus contributing to both 'practice drift' 1 (Maîtrot, 2018) as well as 'mission drift' 2 (Copestake, 2007). In this respect, research has consistently indicated that the regulatory environment is important to microfinance, particularly in periods of crisis (Silva & Chávez, 2015).…”
Section: Background Literature: Microfinance Institutions (Mfis)mentioning
confidence: 99%
“…Microfinance services may therefore be provided by any type of institution, large or small or formal or informal, and can be regulated or unregulated (De' & Ratan, ; Khavul et al, ; Louis et al, ). However, common to most of these institutions is the aim to provide financial services to poor and low‐income people and otherwise marginalized clients (Khavul et al, ; Maîtrot, ; Mersland & Strom, ), who lack access to formal financial services, to finance their entrepreneurial activities and assist them to advance out of poverty (Armendáriz & Morduch, ; Thrikawala, Locke, & Reddy, ). Not only these MFIs do differ in whom they target, their sizes, legal formats, and practice; but also their missions tend to vary a lot.…”
Section: Microfinance and Ictsmentioning
confidence: 99%